Community‐wide seed dispersal distances peak at low levels of specialisation in size‐structured networks. Issue 11 (27th August 2020) - Sorensen, Marjorie C.; Donoso, Isabel; Neuschulz, Eike Lena; Schleuning, Matthias; Mueller, Thomas
Abstract : Network approaches provide insight into the complex web of interspecific interactions that structure ecological communities. However, because data on the functional outcomes of ecological networks are very rarely available, the effect of network structure on ecosystem functions, such as seed dispersal, is largely unknown. Here, we develop a new approach that is able to link interaction networks to a trait‐based seed–dispersal model to estimate community‐wide seed dispersal distances. We simulated networks, using a niche model based on size‐matching between plants and birds, that varied in the degree of niche partitioning, i.e. the overlap in interaction partners between coexisting species. We found that community‐wide dispersal distances were longest when networks had low degrees of niche partitioning. We further found that dispersal distances of plant species with small fruits peaked in models without niche partitioning, whereas dispersal distances of medium and large‐fruited plants peaked at low degrees of niche partitioning. Our simulations demonstrate that the degree of niche partitioning between species is an important determinant of the ecological functions derived from ecological networks and that simulation approaches can provide new insights into the relationship between the structural and functional components of ecological networks.